A Bright Sight of Green Product Market in Malaysia: An Empirical Evidence Using Structural Equation Modelling - Nor Azma Rahlin; Christine J. Gualin (Universal Publishers, 2023)
Purpose: This study aims to examine the influence of environmental concern, utilitarian benefits, and self-expressive benefits on the attitudes toward green cleaning brands. Additionally, the effect of a moderating variable (attitudes toward green cleaning brand) on purchase intention for green brands (cleaning) (PI) this formation process is examined in the context of developing country of green purchasing behavior. Design/methodology/approach: Data were collected using an online self-administered survey to 400 consumers in Malaysia through the purposive sampling method. The model is based on the Theory of Planned Behavior (TPB). Descriptive statistics were analyzed using SPSS, and SmartPLS 3.3.3 was used for; a partial least square-structural equation modelling procedure to analyse the postulated study hypotheses. Findings: The results demonstrate that purchase intention for green brands (cleaning) (PI) was directly and significantly driven by Self-expressive benefits (SE), utilitarian benefits (UB), and environmental concern (EC). Attitude towards green brands (cleaning) mediates the relationship between three antecedents of attitude and purchase intention for green brands (cleaning) (PI). Research limitations/implications: The current study is limited to the geographical area, of Sabah, Malaysia during Covid-19 pandemic. Therefore, generalizability and gain a better knowledge of the overall context is limited. Practical implications: The current model brings a bright sight of the green product market to stakeholders to meet the rising need for ecologically friendly cleaning products and help to improve the environmental sustainability and benefits to the consumer. Directions for further research are suggested. Originality/value: This study guided green firms on cultivating the various behavioral aspects under TPB factors with their consumers over time, with a stronger emphasis on encouraging adoption/purchase behaviors.